Aplicación de la técnica de lamp en el estudio de (Mycobacterium Bovis) en el camal municipal del Cantón El Empalme, Provincia del Guayas 2018. - Palacios Cobeña, Claudio Leonardo (2019)
The study of Mycobacterium bovis in microbiology worldwide due to its social effect on health and economy, due to its zoonotic nature. Bacterium are often transmitted to mammals by spreading by contact with infected domestic or wild animals. The frequent thing is the airway, when coughing or breathing, via the digestive system. It is spread by ingesting raw milk, salivation or other contaminations of contaminated feeders or drinkers. People can infect when drinking or eating unpasteurized dairy products. Raw or undercooked meat can also be a source of transmission. Through direct contact with a wound, what could happen during the handling of animals, killing, transport, Butcher shop. For the determination of the disease, different types of methods and techniques are currently carried out, some in periods of short times, but with a very low specificity, others with long periods of time greater than 48 hours, high costs and low percentage of specificity. In order to validate the efficiency of the LAMP technique in the detection of Mycobacterium bovis. This work is based on the extraction of pulmonary nodules from animals with unfavorable characteristics (low body weight, decay, cough). Subjected 46 animals per week sampled for 8 weeks. DNA was extracted by applying the modified TENS protocol. Following (LAMP) high specificity, efficacy and speed under isothermal conditions, carried out at a constant temperature. Determining the prevalence of bovine infected with Mycobacterium bovis 122 (33.15%) positive and 246 (66.85%) negative that are slaughtered in the slaughter center Municipality of the city El Empalme. Once the process was completed, a cost per sample reaction was obtained with the use of the LAMP technique for the detection of Mycobacterium bovis of $ 1.81, remaining below the cost in comparison with other techniques. Keywords: Respite way, specificity, prevalence.